Work smarter not harder - Collis, Jack; Leboeuf, Michael (New Delhi : Leads Press, 2006)
"Working too hard? Not getting the fulfilment and rewards you want? Do you want your life to be a work of art, rather than a life of work? With a little guidance from Jack Collis and Michael Leboeuf you can find the perfect balance, it$1 (Bs simple. Just work smarter, not harder! Completely revised and updated, Work Smarter, Not Harder, is more than just a business book. It is a clear and effective personal strategy that can help you to make the most of and get most out of your life."--s
Keywords: Organizational effectiveness; Work environment; Time management